Energy extraction and use in a nomadic pastoral ecosystem - Coughenour, M B; Ellis, J E; Swift, D M; Coppock, D L; Galvin, K; McCabe, J T; Hart, T C (Science (American Association for the Advancement of Science), 1985)
An analysis of annual energy flows in an arid tropical ecosystem inhabited by nomadic pastoralists provides insight into a subsistence life-style that has persisted in droughted environments for hundreds to thousands of years. Although a large fraction of the total energy consumed by the Ngisonyoka of Kenya followed a single pathway from plant to animal to human, they also harvested solar energy from a relatively diverse assemblage of energy flow channels. Energy utilization and conversion efficiencies were generally low, as the system is maintenance-rather than production-oriented. Energy flow to maintenance must be relatively high to support biotic responses that enable tolerance of abiotic variability and to stabilize energy flow under the stress of severe droughts. Energy utilization by the Ngisonyoka is therefore consistent with ecological patterns that promote rather than diminish ecological stability under stress.